2009
DOI: 10.1108/13665620910954210
|View full text |Cite
|
Sign up to set email alerts
|

The informal learning of new teachers in school

Abstract: The purpose of this paper is to present what the study of the experiences of beginning teachers and their informal learning says about the process of learning to teach, and to discuss the main emerging themes in relation to a wider literature. The design of the paper is essentially ethnographic and building of grounded theory, based on an accumulation of data derived from interviews with beginning teachers and connecting to extant theory. The findings are that a focus on the informal learning of beginners in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
0
27
0
2
Order By: Relevance
“…Studies on informal learning examined learners from varied organizational settings reflective of business, industry, healthcare, education, and other professional contexts (Cheetham and Chivers, 2001;Gola, 2009;Lohman, 2000Lohman, , 2006McNally et al, 2009;Watkins and Cervero, 2000). Yet, given the importance of informal learning as a critical process in the development of professional knowledge and expertise, scholars indicated that other professions need to be examined to capture variation in worker characteristics and environments (Goldman et al, 2009;Lohman, 2006).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Studies on informal learning examined learners from varied organizational settings reflective of business, industry, healthcare, education, and other professional contexts (Cheetham and Chivers, 2001;Gola, 2009;Lohman, 2000Lohman, , 2006McNally et al, 2009;Watkins and Cervero, 2000). Yet, given the importance of informal learning as a critical process in the development of professional knowledge and expertise, scholars indicated that other professions need to be examined to capture variation in worker characteristics and environments (Goldman et al, 2009;Lohman, 2006).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In most of the papers, emotions are described as explicitly experienced emotions (most often negative emotions, such as fear and insecurity) connected to project failures (Shepherd et al 2011), identity learning (Meijers 2002;Geijsel and Meijers 2005), critical action learning at work (Trehan and Rigg 2015), intercultural learning (Jokikokko and Uitto 2016), or well-being at work (Owen 2016). Two papers further stress negative emotions, such as anxiety, at the start of a new job (McNally et al 2009) or emotional suffering amid tightened government policies in public service work (Colley 2012). Two papers by Rausch et al (2015Rausch et al ( , 2017 describe emotions as emotional states; they refer to the common circumplex model of emotion (e.g.…”
Section: The Understanding Of Emotionsmentioning
confidence: 99%
“…Emotions Influencing Identity Learning All four papers in this sub-category elaborate how emotions that influence identity learning carry forward into teachers' work or career development (Meijers 2002;Geijsel and Meijers 2005;McNally et al 2009;Jakhelln 2010). The papers share the finding that emotions are important in identity learning at the start of one's career and, further, that they constitute an important aspect of workplace learning in the course of one's career.…”
Section: Learning At Work As a Phenomenon Influenced By Emotionsmentioning
confidence: 99%
“…It also provides opportunities for science and technology education (Krishnamurthi & Rennie, 2013). Over the last 20 years quite a few researchers have examined the role of informal science on teacher learning and development (Anderson, Lucas & Ginns, 2003, Anderson, Lawson & Smith, 2006, McNally, Blake & Reid 2009. Built upon this framework, the purpose of this study is to explore how three informal learning approaches can affect preservice teachers' personal philosophies about science teaching.…”
Section: Introductionmentioning
confidence: 99%